Paradigma Baru Perencanaan Pendidikan Islam - Ma’arif, Muhammad Sultanul; Hidayatullah, Risky; Fauziah, Nadhira Laila (Jurnal Pendidikan Islam, 2024)
Islamic education planning has become a crucial element in efforts to enhance relevant and high-quality education in line with the current era's developments. In this modern age, the traditional paradigm in Islamic education planning is insufficient to meet contemporary demands. The new paradigm aims as a step towards the renewal and improvement of Islamic education. The approach of the new paradigm in Islamic education planning can encompass various aspects, including: First, a broader and more efficient integration of information technology. Second, the development of a more contemporary curriculum that is relevant to global challenges. Third, active participation in the community and the implementation of educational plans. Fourth, assigning a greater role to Islamic education in creating positive transformations in the education system. With the introduction of the new paradigm, the goal is to enhance the quality and values of Islamic education.